High borosilicate glass for culture dish and preparation process of high borosilicate glass
By preparing and spraying composite coatings with high borosilicate glass on the surface, it solves its shortcomings in temperature changes and chemical corrosion, significantly improves its heat resistance and corrosion resistance, and meets the demand of modern laboratories for high-performance petri dishes. .
Patent Information
- Application Number
- CN202411600182.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
Existing borosilicate glasses are prone to rupture when subjected to rapid temperature changes and have weak tolerance to corrosion by acids, alkalis and other chemical reagents, which cannot meet the needs of modern laboratories for high-performance petri dishes.
By preparing a borosilicate glass containing silica, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate and lithium oxide, and spraying a composite sol of silicon-aluminum and polydimethyl on its surface evenly A composite coating composed of silicone coatings is UV cured to enhance its heat and corrosion resistance.
The heat resistance, corrosion resistance and mechanical properties of high borosilicate glass for petri dishes are significantly improved, so that it can withstand temperature changes and chemical corrosion more stably, meeting the needs of modern laboratories for high-performance petri dishes.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high borosilicate glass, in particular to high borosilicate glass for culture dishes and a preparation process thereof. Background Art
[0002] As an indispensable basic tool in laboratory applications, the quality of culture dishes directly affects the accuracy and reliability of experimental results. Traditional culture dishes are usually made of ordinary glass or polycarbonate materials, but these materials have limitations in terms of high temperature resistance, chemical corrosion resistance and mechanical strength, and cannot meet the needs of modern laboratories for high-performance culture dishes.
[0003] The main components of high borosilicate glass are silicon dioxide and boron oxide. Compared with ordinary glass, it has higher transparency, so that experimental samples can be clearly observed and analyzed. However, when used, high borosilicate glass is prone to cracking due to rapid temperature changes and is easily corroded by acids, alkalis and other chemical reagents.
[0004] In order to solve the above problems, improve the corrosion resistance and high temperature resistance of high borosilicate glass, and improve its mechanical properties, the present invention provides a high borosilicate glass for a culture dish and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a high borosilicate glass for a culture dish and a preparation process thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation process of high borosilicate glass for culture dishes comprises the following steps:
[0008] Step 1: Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1600-1700°C, melt, pour, keep warm at 550-580°C for 2-3h, cool to 25-30°C, then crystallize and keep warm at 680-700°C for 8-10h, cool to 25-30°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass;
[0009] Step 2: Take the silicon-aluminum composite sol and the polydimethylsiloxane coating, stir them evenly to obtain a composite coating;
[0010] Step 3: Take high borosilicate glass, spray the composite coating evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1-2 minutes to obtain high borosilicate glass for culture dishes.
[0011] More optimally, the preparation method of the polydimethylsiloxane coating comprises the following steps:
[0012] S1: Take vinyl-terminated polydimethylsiloxane and tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take thiocyanate and tetrahydrofuran, stir evenly to obtain a thiocyanate solution; take pentaerythritol triacrylate and tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0013] S2: Take isophorone diisocyanate and tetrahydrofuran, stir evenly, add dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 45-48°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2-2.5h, cool to 25-28°C, add 1,3-propylenediamine dropwise, react for 60-90min, and obtain compound A; add thiocyanate solution dropwise to compound A, heat to 65-70°C, react for 3-5h, and obtain compound B;
[0014] S3: Add pentaerythritol triacrylate solution dropwise to compound B, stir for 3-3.5 hours, rotary evaporate for 5-10 minutes, add 1g 184 photoinitiator, stir evenly, and obtain polydimethylsiloxane coating.
[0015] More optimally, the preparation method of the silica-aluminum composite sol is: take silica-polydimethylsiloxane composite sol and deionized water, mix them evenly to obtain a silica sol mixed solution; mix aluminum isopropoxide and deionized water evenly, use nitric acid to adjust the pH value to 2.5-2.7, and hydrolyze in a water bath of 75-80°C for 9-10h to obtain alumina sol; add the alumina sol dropwise to the silica sol mixed solution, stir evenly, add 3-mercaptopropionic acid, and continue stirring to obtain a silica-aluminum composite sol.
[0016] More optimally, the preparation method of the silica-polydimethylsiloxane composite sol is: take deionized water and catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take tetraethyl orthosilicate and anhydrous ethanol, mix evenly, add the dibutyltin dilaurate solution dropwise, stir for 1-1.5 hours at 25-30°C, add terminal vinyl polydimethylsiloxane, stir for 3-4 hours, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol.
[0017] More optimally, the mass ratio of the silica-alumina composite sol to the polydimethylsiloxane coating is 1:(10-12).
[0018] More optimally, the high borosilicate glass includes the following components, calculated by mass percentage: 80wt%-85wt% of silicon dioxide, 8wt%-12wt% of borax, 5wt%-8wt% of boric acid, 4wt%-8wt% of sodium silicate, 2.5wt%-4.5wt% of aluminum hydroxide, 2wt%-3.5wt% of zirconium phosphate, and 0.2wt%-0.6wt% of lithium oxide.
[0019] More optimally, the thickness of the composite coating is 10-15 μm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention prepares a silicon-aluminum composite sol, introduces alumina sol into silica sol, forms an inorganic network structure that is stable at high temperatures, improves the thermal stability and acid and alkali corrosion resistance of the sol, and thus improves the heat resistance and corrosion resistance of high borosilicate glass for culture dishes.
[0022] 2. When preparing the silicon dioxide-polydimethylsiloxane composite sol, the present invention adds vinyl-terminated polydimethylsiloxane to the sol. The vinyl-terminated polydimethylsiloxane has low surface tension, which improves the high temperature resistance and chemical corrosion resistance of the coating. The present invention adds 3-mercaptopropionic acid to the silicon-aluminum composite sol. Vinyl polydimethylsiloxane can react with it under ultraviolet light, promote cross-linking, enhance the density of the coating, reduce the penetration of chemical media, and further improve the corrosion resistance of high borosilicate glass.
[0023] 3. Polydimethylsiloxane itself has a certain ability to withstand high temperatures. When combined with silicon-aluminum composite sol, it can form a more stable material under high temperature conditions, thereby improving the heat resistance of high borosilicate glass used in culture dishes. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The sources and models of the substances involved in the present invention are not particularly limited, and exemplary include: terminal vinyl polydimethylsiloxane: model: 04268, which can be purchased from Wuhan Kanos Technology Co., Ltd.
[0026] Embodiment 1: A process for preparing high borosilicate glass for culture dishes, comprising the following steps:
[0027] Step 1: Preparation of silica-polydimethylsiloxane composite sol:
[0028] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, drop the dibutyltin dilaurate solution, stir at 28 ° C for 1.2 h, add 5.5 g of vinyl-terminated polydimethylsiloxane, stir for 3.5 h, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol;
[0029] Step 2: Preparation of silicon-aluminum composite sol:
[0030] Take 25g of silica-polydimethylsiloxane composite sol and 25mL of deionized water, mix them evenly to obtain a silica sol mixed solution; mix 3g of aluminum isopropoxide and 80mL of deionized water evenly, adjust the pH value to 2.5 with nitric acid, and hydrolyze in a water bath at 78°C for 9.5h to obtain an alumina sol; add 15g of alumina sol dropwise to the silica sol mixed solution, stir evenly, add 2.5g of 3-mercaptopropionic acid, and continue stirring to obtain a silica-alumina composite sol;
[0031] Step 3: Preparation of polydimethylsiloxane coating:
[0032] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0033] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 46°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2.3h, cool to 27°C, add 0.3g of 1,3-propylenediamine dropwise, react for 80min, and obtain compound A;
[0034] Add thiocyanate solution dropwise to compound A, raise the temperature to 68°C, and react for 4 hours to obtain compound B;
[0035] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3.2 hours, rotary evaporated for 8 minutes, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0036] Step 4: Preparation of borosilicate glass for culture dishes:
[0037] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1650°C, melt, pour, keep warm at 560°C for 2.5 hours, cool to 28°C, then crystallize and keep warm at 690°C for 9 hours, cool to 28°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0038] The high borosilicate glass comprises the following components, calculated by mass percentage: 83wt% silicon dioxide, 10wt% borax, 7wt% boric acid, 6wt% sodium silicate, 3.5wt% aluminum hydroxide, 3.2wt% zirconium phosphate, and 0.4wt% lithium oxide;
[0039] Take 10g of silicon-aluminum composite sol and 110g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0040] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1.5 minutes to obtain high borosilicate glass for culture dishes.
[0041] Embodiment 2: A process for preparing high borosilicate glass for culture dishes, comprising the following steps:
[0042] Step 1: Preparation of silica-polydimethylsiloxane composite sol:
[0043] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, drop the dibutyltin dilaurate solution, stir at 28 ° C for 1 h, add 5.5 g of vinyl-terminated polydimethylsiloxane, stir for 3 h, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol;
[0044] Step 2: Preparation of silicon-aluminum composite sol:
[0045] Take 25g of silica-polydimethylsiloxane composite sol and 25mL of deionized water, mix them evenly to obtain a silica sol mixed solution; mix 3g of aluminum isopropoxide and 80mL of deionized water evenly, adjust the pH value to 2.5 with nitric acid, and hydrolyze in a water bath at 75°C for 9h to obtain an alumina sol; add 15g of alumina sol dropwise to the silica sol mixed solution, stir evenly, add 2.5g of 3-mercaptopropionic acid, and continue stirring to obtain a silica-alumina composite sol;
[0046] Step 3: Preparation of polydimethylsiloxane coating:
[0047] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0048] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 45°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2h, cool to 25°C, add 0.3g of 1,3-propylenediamine dropwise, react for 60min, and obtain compound A;
[0049] Add thiocyanate solution dropwise to compound A, raise the temperature to 65°C, and react for 3 hours to obtain compound B;
[0050] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3 h, rotary evaporated for 5 min, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0051] Step 4: Preparation of borosilicate glass for culture dishes:
[0052] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1600°C, melt, pour, keep at 550°C for 2 hours, cool to 25°C, then crystallize at 680°C for 8 hours, cool to 25°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0053] The high borosilicate glass comprises the following components, calculated by mass percentage: 80wt% silicon dioxide, 8wt% borax, 5wt% boric acid, 4wt% sodium silicate, 2.5wt% aluminum hydroxide, 2wt% zirconium phosphate, and 0.2wt% lithium oxide;
[0054] Take 10g of silicon-aluminum composite sol and 100g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0055] The mass ratio of the silica-alumina composite sol to the polydimethylsiloxane coating is 1:10;
[0056] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1 minute to obtain high borosilicate glass for culture dishes.
[0057] Embodiment 3: A process for preparing high borosilicate glass for culture dishes, comprising the following steps:
[0058] Step 1: Preparation of silica-polydimethylsiloxane composite sol:
[0059] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, drop the dibutyltin dilaurate solution, stir at 30°C for 1.5 h, add 5.5 g of vinyl-terminated polydimethylsiloxane, stir for 4 h, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol;
[0060] Step 2: Preparation of silicon-aluminum composite sol:
[0061] Take 25g of silica-polydimethylsiloxane composite sol and 25mL of deionized water, mix them evenly to obtain a silica sol mixed solution; mix 3g of aluminum isopropoxide and 80mL of deionized water evenly, adjust the pH value to 2.5 with nitric acid, and hydrolyze in a water bath at 80°C for 10h to obtain an alumina sol; add 15g of alumina sol dropwise to the silica sol mixed solution, stir evenly, add 2.5g of 3-mercaptopropionic acid, and continue stirring to obtain a silica-alumina composite sol;
[0062] Step 3: Preparation of polydimethylsiloxane coating:
[0063] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0064] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 48°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2.5h, cool to 28°C, add 0.3g of 1,3-propylenediamine dropwise, react for 90min, and obtain compound A;
[0065] Add thiocyanate solution dropwise to compound A, raise the temperature to 70°C, and react for 5 hours to obtain compound B;
[0066] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3.5 hours, rotary evaporated for 10 minutes, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0067] Step 4: Preparation of borosilicate glass for culture dishes:
[0068] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1700°C, melt, pour, keep at 580°C for 3 hours, cool to 30°C, then crystallize at 700°C for 10 hours, cool to 30°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0069] The high borosilicate glass comprises the following components, calculated by mass percentage: 85wt% silicon dioxide, 12wt% borax, 8wt% boric acid, 8wt% sodium silicate, 4.5wt% aluminum hydroxide, 3.5wt% zirconium phosphate, and 0.6wt% lithium oxide;
[0070] Take 10g of silicon-aluminum composite sol and 120g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0071] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 2 minutes to obtain high borosilicate glass for culture dishes.
[0072] Comparative Example 1: No alumina sol was introduced, and the rest was the same as Example 1:
[0073] Step 1: Preparation of silica-polydimethylsiloxane composite sol:
[0074] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, drop the dibutyltin dilaurate solution, stir at 28 ° C for 1.2 h, add 5.5 g of vinyl-terminated polydimethylsiloxane, stir for 3.5 h, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol;
[0075] Step 2: Preparation of polydimethylsiloxane coating:
[0076] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0077] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 46°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2.3h, cool to 27°C, add 0.3g of 1,3-propylenediamine dropwise, react for 80min, and obtain compound A;
[0078] Add thiocyanate solution dropwise to compound A, raise the temperature to 68°C, and react for 4 hours to obtain compound B;
[0079] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3.2 hours, rotary evaporated for 8 minutes, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0080] Step 3: Preparation of borosilicate glass for culture dishes:
[0081] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1650°C, melt, pour, keep warm at 560°C for 2.5 hours, cool to 28°C, then crystallize and keep warm at 690°C for 9 hours, cool to 28°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0082] The high borosilicate glass comprises the following components, calculated by mass percentage: 83wt% silicon dioxide, 10wt% borax, 7wt% boric acid, 6wt% sodium silicate, 3.5wt% aluminum hydroxide, 3.2wt% zirconium phosphate, and 0.4wt% lithium oxide;
[0083] Take 10g of silicon dioxide-polydimethylsiloxane composite sol and 110g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0084] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1.5 minutes to obtain high borosilicate glass for culture dishes.
[0085] Comparative Example 2: No 3-mercaptopropionic acid was added, and the rest was the same as Example 1:
[0086] Step 1: Preparation of silica-polydimethylsiloxane composite sol:
[0087] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, drop the dibutyltin dilaurate solution, stir at 28 ° C for 1.2 h, add 5.5 g of vinyl-terminated polydimethylsiloxane, stir for 3.5 h, and stand for aging to obtain a transparent silica-polydimethylsiloxane composite sol;
[0088] Step 2: Preparation of silicon-aluminum composite sol:
[0089] Take 25g of silica-polydimethylsiloxane composite sol and 25mL of deionized water, mix them evenly to obtain a silica sol mixed solution; mix 3g of aluminum isopropoxide and 80mL of deionized water evenly, adjust the pH value to 2.5 with nitric acid, and hydrolyze in a water bath at 78°C for 9.5h to obtain an alumina sol; add 15g of alumina sol dropwise to the silica sol mixed solution, stir evenly, and obtain a silica-alumina composite sol;
[0090] Step 3: Preparation of polydimethylsiloxane coating:
[0091] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0092] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 46°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2.3h, cool to 27°C, add 0.3g of 1,3-propylenediamine dropwise, react for 80min, and obtain compound A;
[0093] Add thiocyanate solution dropwise to compound A, raise the temperature to 68°C, and react for 4 hours to obtain compound B;
[0094] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3.2 hours, rotary evaporated for 8 minutes, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0095] Step 4: Preparation of borosilicate glass for culture dishes:
[0096] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1650°C, melt, pour, keep warm at 560°C for 2.5 hours, cool to 28°C, then crystallize and keep warm at 690°C for 9 hours, cool to 28°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0097] The high borosilicate glass comprises the following components, calculated by mass percentage: 83wt% silicon dioxide, 10wt% borax, 7wt% boric acid, 6wt% sodium silicate, 3.5wt% aluminum hydroxide, 3.2wt% zirconium phosphate, and 0.4wt% lithium oxide;
[0098] Take 10g of silicon-aluminum composite sol and 110g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0099] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1.5 minutes to obtain high borosilicate glass for culture dishes.
[0100] Comparative Example 3: Polydimethylsiloxane itself is not compounded with the silicon-aluminum composite sol, and the rest is the same as Example 1:
[0101] Step 1: Preparation of silica sol:
[0102] Take 3 mL of deionized water and 0.3 g of catalyst dibutyltin dilaurate, stir evenly to obtain a dibutyltin dilaurate solution; take 27.5 g of tetraethyl orthosilicate and 85 mL of anhydrous ethanol, mix evenly, add the dibutyltin dilaurate solution dropwise, stir at 28 ° C for 3 h, and let stand for aging to obtain a transparent silica sol;
[0103] Step 2: Preparation of silicon-aluminum composite sol:
[0104] Take 25g of silica sol and 25mL of deionized water, mix them evenly to obtain a silica sol mixed solution; mix 3g of aluminum isopropoxide and 80mL of deionized water evenly, adjust the pH value to 2.5 with nitric acid, and hydrolyze in a water bath at 78°C for 9.5h to obtain an alumina sol; add 15g of alumina sol dropwise to the silica sol mixed solution, stir evenly, add 2.5g of 3-mercaptopropionic acid, and continue stirring to obtain a silica-alumina composite sol;
[0105] Step 3: Preparation of polydimethylsiloxane coating:
[0106] Take 25g of vinyl-terminated polydimethylsiloxane and 200mL of tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take 3.5g of thiocyanuric acid and 100mL of tetrahydrofuran, stir evenly to obtain a thiocyanuric acid solution; take 7g of pentaerythritol triacrylate and 50mL of tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution;
[0107] Take 6g of isophorone diisocyanate and 100mL of tetrahydrofuran, stir evenly, add 0.1g of catalyst dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 46°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2.3h, cool to 27°C, add 0.3g of 1,3-propylenediamine dropwise, react for 80min, and obtain compound A;
[0108] Add thiocyanate solution dropwise to compound A, raise the temperature to 68°C, and react for 4 hours to obtain compound B;
[0109] The pentaerythritol triacrylate solution was added dropwise to compound B, stirred for 3.2 hours, rotary evaporated for 8 minutes, 1 g of 184 photoinitiator was added, and stirred evenly to obtain a polydimethylsiloxane coating;
[0110] Step 4: Preparation of borosilicate glass for culture dishes:
[0111] Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1650°C, melt, pour, keep warm at 560°C for 2.5 hours, cool to 28°C, then crystallize and keep warm at 690°C for 9 hours, cool to 28°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass with a thickness of 5 mm;
[0112] The high borosilicate glass comprises the following components, calculated by mass percentage: 83wt% silicon dioxide, 10wt% borax, 7wt% boric acid, 6wt% sodium silicate, 3.5wt% aluminum hydroxide, 3.2wt% zirconium phosphate, and 0.4wt% lithium oxide;
[0113] Take 10g of silicon-aluminum composite sol and 110g of polydimethylsiloxane coating, stir evenly to obtain a composite coating;
[0114] Take high borosilicate glass, spray a layer of composite coating with a thickness of 5 μm evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1.5 minutes to obtain high borosilicate glass for culture dishes.
[0115] experiment:
[0116] The performance test was performed on the culture dishes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 using high borosilicate glass. A 3 mm × 100 mm × 100 mm culture dish was tested for impact resistance using a drop ball impact tester. The mass of the steel ball was 300 g. The steel ball was free-fall impacted from 30 cm above the nine-square grid on the glass surface, with a height increase of 5 cm. Each height point was impacted twice, and the lowest height when broken was tested.
[0117] Take a 3mm×400mm×200mm culture dish made of high borosilicate glass and refrigerate it at 4℃ for 3h, then pour hot water preheated to different temperatures on the glass surface, starting from 40℃. After each pouring, if the glass does not crack, put it back into the refrigerator and refrigerate it again. After taking it out again, preheat the hot water temperature to 5℃ higher than the last pouring hot water temperature until the glass cracks. The cracking temperature indicates the high temperature resistance of the product.
[0118] Take a 3mm×100mm×100mm culture dish with high borosilicate glass for corrosion resistance test. Soak the high borosilicate glass in 2% sulfuric acid solution for 30 days and calculate the weight loss rate; weight loss rate = (weight before soaking - weight after soaking) / weight before soaking. The data are shown in the following table:
[0119] Impact resistance / cm High temperature resistance / ℃ Weight loss rate / % Example 1 35 95 0.006 Example 2 30 95 0.007 Example 3 35 95 0.006 Comparative Example 1 30 80 0.012 Comparative Example 2 30 85 0.011 Comparative Example 3 30 80 0.014
[0120] Conclusion: Comparative Example 1 does not introduce alumina sol, and the heat resistance and corrosion resistance of the high borosilicate glass for culture dishes decrease. Comparative Example 2 does not add 3-mercaptopropionic acid, the density of the coating decreases, the corrosion resistance of the high borosilicate glass decreases, and the high temperature resistance decreases. Comparative Example 3 does not compound polydimethylsiloxane itself with the silica-alumina composite sol, and the heat resistance and corrosion resistance of the high borosilicate glass for culture dishes decrease. In Examples 1-3 of the present invention, alumina sol is introduced into silica sol to form an inorganic network structure that is stable at high temperatures, thereby improving the thermal stability and acid and alkali corrosion resistance of the sol. 3-mercaptopropionic acid is added to the silica-alumina composite sol, and vinyl polydimethylsiloxane can react with it under ultraviolet light to promote crosslinking, enhance the density of the coating, reduce the penetration of chemical media, and further improve the corrosion resistance of the high borosilicate glass.
[0121] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing high borosilicate glass for culture dishes, characterized in that: The following steps are involved: Step 1: Take silicon dioxide, borax, boric acid, sodium silicate, aluminum hydroxide, zirconium phosphate, and lithium oxide, heat to 1600-1700°C, melt, pour, keep warm at 550-580°C for 2-3h, cool to 25-30°C, then crystallize and keep warm at 680-700°C for 8-10h, cool to 25-30°C, cut, grind, polish, clean, and dry to obtain high borosilicate glass; Step 2: Take the silicon-aluminum composite sol and the polydimethylsiloxane coating, stir them evenly to obtain a composite coating; Step 3: Take high borosilicate glass, spray the composite coating evenly on the surface of the high borosilicate glass, and then cure it under a UV lamp for 1-2 minutes to obtain high borosilicate glass for culture dishes.
2. The process for preparing high borosilicate glass for a culture dish according to claim 1, characterized in that: The preparation method of the polydimethylsiloxane coating is: The following steps are involved: S1: Take vinyl-terminated polydimethylsiloxane and tetrahydrofuran, stir evenly to obtain a vinyl-terminated polydimethylsiloxane solution; take thiocyanate and tetrahydrofuran, stir evenly to obtain a thiocyanate solution; take pentaerythritol triacrylate and tetrahydrofuran, stir evenly to obtain a pentaerythritol triacrylate solution; S2: Take isophorone diisocyanate and tetrahydrofuran, stir evenly, add dibutyltin dilaurate dropwise, stir evenly, introduce nitrogen, heat to 45-48°C, add vinyl-terminated polydimethylsiloxane solution dropwise, react for 2-2.5h, cool to 25-28°C, add 1,3-propylenediamine dropwise, react for 60-90min, and obtain compound A; add thiocyanate solution dropwise to compound A, heat to 65-70°C, react for 3-5h, and obtain compound B; S3: Add pentaerythritol triacrylate solution dropwise to compound B, stir for 3-3.5 hours, rotary evaporate for 5-10 minutes, add 1g 184 photoinitiator, stir evenly, and obtain polydimethylsiloxane coating.
3. The process for preparing high borosilicate glass for a culture dish according to claim 1, characterized in that: The preparation method of the silica-alumina composite sol is as follows: taking silica-polydimethylsiloxane composite sol and deionized water, mixing them evenly to obtain a silica sol mixed solution; mixing aluminum isopropoxide and deionized water evenly, adjusting the pH value to 2.5-2.7 with nitric acid, and hydrolyzing in a water bath of 75-80° C. for 9-10 hours to obtain alumina sol; dropping the alumina sol into the silica sol mixed solution, stirring evenly, adding 3-mercaptopropionic acid, and continuing to stir to obtain a silica-alumina composite sol.
4. The process for preparing high borosilicate glass for a culture dish according to claim 3, characterized in that: The preparation method of the silica-polydimethylsiloxane composite sol is as follows: taking deionized water and a catalyst dibutyltin dilaurate, stirring evenly to obtain a dibutyltin dilaurate solution; taking tetraethyl orthosilicate and anhydrous ethanol, mixing evenly, adding the dibutyltin dilaurate solution dropwise, stirring at 25-30° C. for 1-1.5 hours, adding vinyl-terminated polydimethylsiloxane, stirring for 3-4 hours, standing and aging to obtain a transparent silica-polydimethylsiloxane composite sol.
5. The process for preparing high borosilicate glass for a culture dish according to claim 1, characterized in that: The mass ratio of the silica-alumina composite sol to the polydimethylsiloxane coating is 1:(10-12).
6. The process for preparing high borosilicate glass for a culture dish according to claim 1, characterized in that: The high borosilicate glass includes the following components, calculated by mass percentage: 80wt%-85wt% of silicon dioxide, 8wt%-12wt% of borax, 5wt%-8wt% of boric acid, 4wt%-8wt% of sodium silicate, 2.5wt%-4.5wt% of aluminum hydroxide, 2wt%-3.5wt% of zirconium phosphate, and 0.2wt%-0.6wt% of lithium oxide.
7. The process for preparing high borosilicate glass for a culture dish according to claim 1, characterized in that: The thickness of the composite coating is 10-15 μm.
8. The high borosilicate glass for culture dishes prepared according to the preparation process of high borosilicate glass for culture dishes according to any one of claims 1 to 7.